Factors influencing unemployment among graduates: a case study in Shah Alam / Nur A'amilyn Abdul Halim - Abdul Halim, Nur A'amilyn (Faculty of Business and Management, 2019)
Malaysian graduates have faced issue of unemployment, as years go by, the numbers of unemployment among graduates has risen. Unemployment indicates the total number of people who are willing to work however did not have a job. Whereas, all graduates desire is getting jobs since it is the purpose for their studies. The unemployment rate among fresh graduates in Malaysia have increased from 30% in 2013 to 34% in 2016. As stated by the Department of Statistics Malaysia, the total unemployment number in Selangor is approximately 98,000 over 4. I million population of people in Selangor as of 2017. The increasing unemployment rate is a grave concern since this issue will decrease the image of educational system in Malaysia and hence lead the companies or employees lost interest in our local graduates if the root causes of the matter have not been identified. This paper examined the reasons and factors why graduates are facing unemployment in the competitive market in Shah Alam, Malaysia. 159 data of graduates were collected in Shah Alam and analysed using Statistical Package for Social Science (SPSS). The respondents comprised from a group of workers in Shah Alam which graduated from higher institutions and experience unemployment not less than six months from the date they finished their studies until they finally got employed. Several factors such as graduate attributes, employability skills, English proficiency, unrealistic salary and job mismatch were determined their relevancy towards unemployment among graduates in Shah Alam. The result of the study presented in this research agrees that graduate attributes and job